Penerapan Metode MAUT dalam Menentukan Lokasi Cabang Baru Tokepangsit Medan di Kabupaten Langkat - Silvia Amara; Cinta Apriliza; Sherly Rohana; Amirullah Wahid; Safrizal Safrizal (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Every business definitely wants to expand its business by opening new branches in different regions to increase income and become a successful business. To open a new business branch, of course, a lot of consideration is needed before making a decision. So that the decision is correct and in accordance with needs, Research is used in its implementation. Therefore, this research applies a decision support system using the Multi Attribute Utility Theory (MAUT) method in selecting a new branch location for the Tokepangsit Medan business which will open a new branch in Langkat Regency. With this method, the decision result obtained is alternative 4, namely Selesai District, which gets the highest score of 0.640.